Peran Komunikasi Terapeutik Dalam Meningkatkan Kesiapan Psikologis Pasien Pra Operasi - Najwa Syifa Aqilla; Dr.Taufik Akhyar; M. Arif Setiawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Preoperative patients commonly experience anxiety, fear, and uncertainty, which can affect their psychological preparedness for surgery. This situation requires healthcare professionals to play a role not only in the medical aspect but also in a therapeutic communication approach. This study aims to analyze the application of therapeutic communication in improving preoperative patient psychological preparedness and identify supporting and inhibiting factors in the Central Surgical Installation of dr. Rivai Abdullah Banyuasin General Hospital. The study used a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation studies. Informants included surgeons, nurses, and preoperative patients. The results indicate that empathetic, informative, and supportive therapeutic communication can reduce anxiety and increase patient self-confidence. However, time constraints and the workload of healthcare professionals remain barriers to its implementation.